Making medicine scientific : John Burdon Sanderson and the culture of Victorian science - Romano, Terrie M. (Johns Hopkins University Press, 2002)
Romano's detailed portrayal reveals a fascinating figure who embodied the untidy nature of the Victorian age's shift from an intellectual system rooted in religion to one based on science.